Effect of chitosan on activities of enzymes relating to resistance of tea plant - SUN Shi-li; LUO Yao-ping (浙江大学学报. 农业与生命科学版)
Effects of chitosan on activities of super oxide dismutase (SOD), peroxidase (POD) and phenylalanine ammonia lyase (PAL) by foliar spraying in tea plants (Camellia sinensis cv. Zhenong 21, Zhenong 113 and Zhenong 139) were investigated. The results show that activities of SOD, POD and PAL in tea leaves were influenced by chitosan. The responses of the enzymes in various tea cultivars to chitosan were differentiated. SOD activities of Zhenong 21, Zhenong 113 and Zhenong 139 were increased by 106.87%, 58.55% and 68.2% when chitosan concentrations were at 200, 100, 200 mg·L-1, respectively. POD activities were increased by 18.47%, 20% and 18.68% when chitosan concentrations were at 200,200,300 mg·L-1, respectively. PAL activities were increased by 33.55%, 12.16% and 31.33% when chitosan concentrations were at 200, 300, 100 mg·L-1, respectively. The study suggests that chitosan might have the potential to enhance the stress resistance of tea plants.